INOVASI DALAM MANAJEMEN PENDIDIKAN: SEBUAH TINJAUAN LITERATUR TERHADAP METODE DAN PRAKTIK TERBARU - Isny Lellya (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Amidst rapid changes in the global education landscape, an in-depth understanding of innovative management practices is becoming increasingly crucial to improving the eflectiveness and efficiency of education systems. The review in this study used the literature method. The review identified five main trends in education management innovation: (1) integration of AI and big data technologies in administrative decision- making, (2) learner-centred design-based management approaches, (3) collaborative leadership models and distribution of responsibilities, (4) adaptive and growth-oriented human resource management strategies, and (5) implementation of circular economy principles in education facility management. The results of this study show that these innovations have the potential to improve operational efficiency, enrich learning experiences, and increase the resilience of educational institutions to external changes. However, their implementation also faces challenges such as change resistance, limited resources and the digital divide